Graphic L.A. - Ruppel, Robh (Culver City, CA : Design Studio Press, 2014)
Graphic L.A. is part practical instruction, part guided meditation on the importance of color values and objects in art. The reader is led by the professional instruction of Robh Ruppel; instructor at the Art Center College of Design, Gnomon School of Visual Effects, and Concept Art Academy. He is also a multiple award-winning art director of video games. By reducing environments down to basic shapes and colors (or "symbols"), Robh builds astounding images. Robh documents the progression of building an image while referencing basic techniques. By using color with surprisingly bold brushstrokes, he produces images of incredible depth with intricate handling of light and shadow. It is a rare exploration into simplicity without resorting to minimalism. Readers will be certain to take away both a sense of admiration for Robh Ruppel's work and a greater understanding and appreciation for the importance of color value relationships in all forms of art.
Keywords: Drawing -- Technique; Form (Aesthetics); Proportion (Art); Graphic arts